2017
DOI: 10.5433/1679-0359.2017v38n5p3145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flunixin Meglumine administration on seminal characteristics of male sheep and goat

Abstract: Testicular degeneration is a multifactorial process increasing the concentration of prostaglandins in seminal plasma. Both increase and decrease of these hormones tend to promote loss of seminal quality. Flunixin meglumine is a potent anti-inflammatory drug capable of modulating the production of prostaglandins and is widely used in female reproduction. However, it is rarely used in males with the same objective. Therefore, this study aimed to evaluate the effects of this drug on seminal quality of male lambs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The drug works by reduces prostaglandins concentration in the epididymis which is essential for sperm production and viability (Dacheux et al 2016). Flunixin meglumine activity in the epididymis enables the formation of a conducive environment for sperm viability, which may improve seminal quality after drug application (Neto et al 2017). Another study by Neto et al (2017) stated that the post-treatment with flunixin meglumine indicated a significant improvement of seminal characteristics related to sperm motility and quantitative numbers of semen and normal sperm and minor and major defects in bucks and rams.…”
Section: Efficacy Of Flunixin Meglumine and Oxytetracycline Used In R...mentioning
confidence: 99%
“…The drug works by reduces prostaglandins concentration in the epididymis which is essential for sperm production and viability (Dacheux et al 2016). Flunixin meglumine activity in the epididymis enables the formation of a conducive environment for sperm viability, which may improve seminal quality after drug application (Neto et al 2017). Another study by Neto et al (2017) stated that the post-treatment with flunixin meglumine indicated a significant improvement of seminal characteristics related to sperm motility and quantitative numbers of semen and normal sperm and minor and major defects in bucks and rams.…”
Section: Efficacy Of Flunixin Meglumine and Oxytetracycline Used In R...mentioning
confidence: 99%